TechTreat Revolutionizing CBT for Chronic Anxiety in Adolescents through Digital Therapeutic Interventions - Wajiha Ghazal; Hifza Qayyum; Noor Zainab; Maryam Khan (Research Journal of Psychology, 2025)
Background: The mental health of the youth these days is increasingly worrisome due to high levels of anxiety. Because of this, new, easier to access treatment strategies are required. Digital cognitive behavioral therapy (CBT) treats patients with AI-powered mobile applications, making it a great substitute for face-to-face therapy. Aim: This study seeks to measure the changes in anxiety symptoms of adolescents with chronic anxiety after applying the TechTREAT intervention, which was developed specifically for this study, in comparison with the traditional in-person CBT therapy. Method: A mixed method study was conducted among 150 adolescents suffering from chronic anxiety. It was divided into two groups: the experimental group received Woebot-based intervention while the control group received traditional CBT. Self-reported anxiety scores were collected before treatment, during week 6, and after week 8 after the treatment. Levels of anxiety during the treatment were measured with standardized instruments that were paired and t-test tested. Results: The experimental group showed a more pronounced decrease in anxiety than the control group; Woebot users were more engaged and were better at symptom self-management. Improved outcomes were facilitated by AI-enabled guidance during exposure exercises, augmented mood monitoring, and feedback tailoring – justifying the use of digital CBT. Conclusion: TechTREAT is proven to lower anxiety for adolescents as well as being an easily adopted and flexible method to implement into a healthcare system which would improve healthcare and therapeutic results.